PENGARUH DIAMETER POHON, UMUR DAN KADAR STIMULAN TERHADAP PRODUKTIVITAS GETAH - R Sudradjat; Dendi Setyawan; S Sumadiwangsa (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
This report revealed the results of assesing the effect of diameter of pine trees, ages and dosages of stimulants (i.e. socepas agent). and harvesting period on the productivity of their exudates. The growing sites of the harvested pine trees were situated at three different blocks (i.e. I, II. and III). These blocks could represent the ages of the standing pine trees (i.e. 15. 18. 24 years old). Ages of trees in block III were the oldest, followed by that of blocks I and II, as consecutively, the youngest and second youngest. The three blocks further were each divided administratively into their own regional areas, called a stripes.For block I. the averages of exudate production varies in the range of 44.63 - 120.25 gram/ tree/period. Different dosages of socepas agent effected significantly the exudates productivity, i.e. the highest at 15 percent socepas agent (i.e. 80.08 gram/tree/period),followed in decreasing order at 20 percent socepas agent (76. 76 gram/tree/period). and at 10 percent socepas agent (61. 79 gram/tree/period). and finally at zero percent stimulant or control (47.81 gram/tree/period). Different harvesting periods. however. did not affect the exudates productivity significantly. Conversely, the diameter of pine trees affected significantly the productivity with a positive linear trend. This trend applied to whatever stripes in which the harvested trees were situated.For block II, harvesting period brought about significant effect on productivity where the highest was obtained at the second period (62.89 gram/tree). followed by decreasing order at the third period (56.31 gram/tree). and at the first period (47. 71 gram/tree), respectively. The variation of exudate productivity was around 39.21 - 81.97 gram/tree/period. This productivity was significantly affected by dosages of socepas. where the highest was at 20 percent dosage (68.08 gram/tree/period). followed at 10 percent (54. 04 gram/tree/period).at 15 percent (52.15 gram/tree/period), and finally at zero percent stimulant or control (48.35 gram/tree/period).Similar in block I. there was positive linear trend between tree diameter and exudates productivity of the pine trees, regardless of their locations in stripes.For block III. harvesting periods also affected the productivity, where the highest was from the third period (50. 71 gram/tree), subsequently from second (49.89 gram/tree). and at last from the first period (43.56 gram/tree). The productivity indicated some variation in the range of 36.06 - 68.34 gram/tree/period.Socepas stimulant affected significantly the exudates production. i.e. the highest at 20 percent socepas (54. 71 gram/tree/period). followed consecutively at 15 percent socepas (51.05 gram/tree/period). at 10 percent (44.28 gram/tree/period). and ultimately at zero percent socepas (42.17 gram/tree/ period). Similar also in blocks I and II. positive linear trend occurred between exudates production and diameters of trees, despite being in different stripes.Ages of the pine trees. as represented by the different blocks, affected production. in that the older the ages the lower the exudates productivity. The average productivities from the trees in block I (as the youngest i.e. 15 years old) and in block II (as the second youngest i.e. 18 years old) were 71.46 gram/tree and 46.07 gram/tree, respectively. Meanwhile, the productivity from block III (as the oldest i.e. 24 years old) was 41.17 gram/tree.